The Implementation of Virtual Classroom in English for Aviation - Ahmad Rossydi; Maya Masita (Universitas Cokroaminoto Palopo, 2021)
The shift of language learning from face-to-face classroom interaction to online learning beyond the classroom amidst the global pandemic of Covid-19 has changed how teachers and students deal with teaching and learning activities. Information and communication technology development, the nature of this engagement must be adapted to fit the hybrid approach of teaching and learning. In this qualitative study, observation and interviews were conducted to explore the implementation and investigate the learners’ perception of a virtual classroom in English for Aviation. An interactive model of data analysis was done for the observation sheet and interviewed data. The main findings were implementing a virtual classroom could build a relationship, increase engagement between teachers and students, and students’ participation in the classroom.